Characterization and antiviral activity of a newly identified defensin-like peptide, HEdefensin, in the hard tick Haemaphysalis longicornis - Talactac, Melbourne Rio; Yada, Yurika; Yoshii, Kentaro; Hernandez, Emmanuel Pacia; Kusakisako, Kodai; Maeda, Hiroki; Galay, Remil Linggatong; Fujisaki, Kozo; Mochizuki, Masami; Tanaka, Tetsuya (Developmental and comparative immunology, 2017)
Tick defensins are antimicrobial peptides that play a major role in the innate immunity of ticks by providing a direct antimicrobial defense. In this study, we identified and characterized a defensin-like encoding gene, HEdefensin, from the expressed sequence tags (EST) database of hemolymph from the hard tick Haemaphysalis longicornis. Expression of the gene in whole adult ticks and in different organs was upregulated during blood feeding, though not after Langat virus (LGTV) challenge. A synthetic HEdefensin peptide demonstrated significant virucidal activity against LGTV but not against an adenovirus in co-incubation virucidal assays. Moreover, the RNAi-mediated gene silencing of HEdefensin did not significantly affect the virus titer as compared to the control group. The data reported here have established the in vitro virucidal activity of the peptide against LGTV. However, its role in the innate antiviral immunity of H. longicornis remains to be explored, and further studies are needed to fully evaluate the potential biological activities of the peptide against bacteria, fungi or parasites. [Display omitted] •The HEdefensin gene was identified from the hemolymph EST database of H. longicornis.•The HEdefensin peptide has virucidal activity against LGTV in vitro.•The HEdefensin gene may not be involved in antiviral immunity against LGTV in vivo.